DINAMIKA PEMBARUAN HUKUM KELUARGA DI NEGARA UNI EMIRAT ARAB - Mulyana, Willy; Nurrahman, Panji; Syawal Rosyid, Muhammad (Usroh, 2024)
Reforms to Islamic family law have been carried out by many Muslim countries. The aim of this reform is to produce legal products that suit the needs of modern society in the country. One of the countries that has reformed Islamic family law is the United Arab Emirates. The United Arab Emirates is reforming Islamic Family Law by re-interpreting the texts of the Al-Qur'an and Hadith and based on the principles of family law in the Maliki school of thought. This research aims to find out the dynamics of Islamic family law reform in the United Arab Emirates. This research is a type of library research. Data was collected using documentation techniques, namely collecting written data in the form of scientific articles resulting from research and books related to research. The results of this research found that the United Arab Emirates first codified family law in 1985. Then in 2005 it reformed its family law by issuing Federal Law Number 28 of 2005 concerning Personal Legal Status. In carrying out family law reforms, the United Arab Emirates uses the talfiq and ijtihad methods. The elements of reform in Federal Law Number 28 of 2005 concerning Personal Legal Status include; marriage, marriage agreements and registration, the age of consent to marry and kafa'ah, the relationship between husband and wife, divorce, and khuluk.